Fundamental rights: the law on the inclusion of the disabled and the right to equality - Fernandes, David Augusto (2019)
This paper aims to present the inclusion of people with disabilities in society, based on several legal systems and, particularly, on the Statute of the Person with Disabilities. It focuses how these people find difficult to take part equally in the social network. This obstacle goes against the universal human rights rules that generally establish the right to dignity as an essential principle and obligation of the State to ensure the equality of such persons as they are able to take part actively in the social environment. This work followed a methodology based on a critical approach to the national and international legal systems and on a discussion of doctrinal positions, in order to aim at the ideal position of the State on taking best proceedings to benefit these people.